Functional materials for solar thermophotovoltaic devices in energy conversion applications: a review - Dada, Modupeola; Popoola, Patricia; Alao, Alice; Olalere, Folasayo; Mtileni, Evlly; Lindokuhle, Ntanzi; Shamaine, Makinita (Frontiers in Energy Research, 2023)
Fossil fuels are now used to meet over 80% of the world’s energy demands, but they have the disadvantages of being unsustainable economically and polluting the environment. Solar energy is also one of the most desired alternative forms of renewable energy due to the quantity of direct sunlight among these sources. Due to the difficulties with solar cells, less than 1% of this energy is harvested and transformed into electricity. Notably, solar thermal and photovoltaic systems are the traditional methods for converting solar energy into electricity. It can be challenging to turn the solar energy captured by these systems into power. In contrast to conventional conversion methods, which involve converting solar energy directly into electricity, this article conducts a thorough investigation of solar thermophotovoltaic devices and the high-tech materials used in solar thermophotovoltaic systems as a solution to the conversion challenges.